Deconstruction and Reconstruction: New Ideas for Refining Teaching Materials on Education for Ethnic Unity and Progress —Starting from the textbook Great Unity of the Chinese Nation - Tang, Miaomiao (Journal of Research in Vocational Education, 2026)
With the popularization and application of teaching materials for education on ethnic unity and progress, frontline teachers are particularly concerned about the interpretive approaches and response strategies embedded in the textbooks. In terms of textbook use, current problems include a mismatch between topic (issue) design and classroom practice, insufficient alignment between ways of presenting content and students’ cognitive characteristics, and weak content systematicity with fractured articulation across schooling stages. To improve the effectiveness of textbook use, it is necessary to update usage concepts so that curricular content and curricular philosophy are organically integrated; innovate methods by relying on scenario-based teaching to help students deepen understanding; and enhance the user experience by developing scientifically sound, activity-based instructional design plans.